Effects of economic growth, foreign direct investment, energy consumption, and urbanization on the ecological footprint in Vietnam - Thao, Bui Thi Thu; Huy, Cao Tan (Tạp chí Nghiên cứu Tài chính - Marketing, 2024)
This research examines the impacts of economic growth, foreign direct investment, energy consumption, and urbanization on the ecological footprint in Vietnam from 1992 to 2022. The Wavelet Coherence analysis method is employed to evaluate the correlation levels between variables across various periods and frequencies, providing insights into the mechanisms and extent to which these factors influence the environment amidst urbanization and economic development. The research results indicate a robust in-phase relationship among energy consumption, urbanization, and the ecological footprint. Meanwhile, the interaction between economic growth, foreign direct investment, and the ecological footprint is observed to be more intricate and fluctuates over time. Drawing from these insights, the authors recommend adopting targeted sustainable development policies, promoting clean energy usage, and implementing effective urban management strategies to mitigate the adverse environmental impacts of economic growth in Vietnam.